Optimization of solid-phase microextraction (SPME) of volatile organic compound (VOC) in dragon fruits / Muhammad Hazwan Dinhusain Johari - Johari, Muhammad Hazwan Dinhusain (2020)
This study was performed to optimize the extraction of volatile organic compounds (VOCs) from dragon fruit using headspace solid-phase microextraction (SPME). The extraction temperature used was 60 °C, 70 °C and 80 °C with the addition of sodium chloride (NaC1). The extraction was analyzed into the gas chromatography-mass spectrum (GC-MS). The effect of sodium chloride(NaC1) addition was also investigated and found better extraction with the addition of sodium chloride at 80 °C extraction temperature. Since it gives 30 numbers of peaks and showed a higher percentage of possibility compound.